In Vivo and Ex Vivo Regulation of Breast Cancer Resistant Protein (Bcrp) by Peroxisome Proliferator-Activated Receptor Alpha (Pparα) at the Blood-Brain Barrier - Hoque, Md. Tozammel (J Neurochem, 2015)
Breast cancer resistance protein (Bcrp/Abcg2) localized at the blood-brain barrier (BBB) limits permeability into the brain of many xenobiotics, including pharmacological agents. Peroxisome proliferator-activated receptor α (Pparα), a ligand-activated transcription factor, primarily involved in lipid metabolism, has been shown to regulate the functional expression of Bcrp in human cerebral microvascular endothelial cells (hCMEC/D3). The aim of this study was to investigate ex vivo and in vivo, the regulation of Bcrp by Pparα in an intact BBB. Ex vivo quantitative real-time PCR and immunoblot analyses showed significant upregulation of Abcg2/Bcrp mRNA and protein levels in CD-1 mouse brain capillaries incubated with clofibrate, a Pparα ligand. Fluorescence-based transport assays in CD-1 and C57BL/6 brain capillaries showed that exposure to clofibrate significantly increased Bcrp transport activity. This increase was not observed in capillaries isolated from Pparα knockout mice. In vivo, we found: i) significant Bcrp protein upregulation in clofibrate dosed CD-1 and C57BL/6 capillary lysates but no effect in Pparα knockout capillary lysates, and ii) significantly increased Bcrp transport activity in capillaries isolated from clofibrate treated mice. These results demonstrate an increase in Bcrp functional expression by Pparα in brain capillaries, and suggest that Pparα is another nuclear receptor that can contribute to the regulation of membrane efflux transporters and drug permeability at the BBB.